The worldview of the pilgrim and the foundation of a confessional and narrative philosophy of education - Braun, Guilherme J. (HTS teologiese studies, 2019)
In this article, we explore the worldview of the pilgrim and how it relates to the drama of human existence. The worldview of the pilgrim is the starting point in our explorations of the postmodern conundrum and interrelated subjects such as epistemology, ethics, religious symbolism, hospitality and practical life strategies from a narrative and confessional perspective. These elaborations will serve the ultimate goal of this article, which is to contribute to the philosophy of education (including educators and educationists) and consequently to equip individuals with skills and substantial knowledge that would allow them to understand, define and pursue their own life goals as well as to participate with integrity in their community as full-fledged, responsible citizens.